Exploring Madurese Language Maintenance Strategies at Pondok Pesantren Al-Hikam Burneh Bangkalan: A Sociolinguistic Study - Zulkhaeriyah Zulkhaeriyah; Bima Kurniawan; Dede Rosyadi ZA; Amalia Hasan (Anaphora : Journal of Language, Literary, and Cultural Studies, 2026)
The increasing influence of globalization and modernization has intensified language shift, placing many regional and minority languages at risk of reduced use and weakened intergenerational transmission. In multilingual contexts such as Indonesia, maintaining local languages has become increasingly important for preserving cultural identity and linguistic diversity. This study aims to explore the sociolinguistic factors and language maintenance strategies supporting Madurese language maintenance at Pondok Pesantren Al-Hikam Burneh, Bangkalan. Using a qualitative descriptive approach, data were collected through semi-structured interviews with 12 participants, consisting of 10 santri (students), 1 ustadz (Islamic teachers), and 1 Head of Student Board selected through purposive sampling. The findings reveal that key sociolinguistic factors identified by Fishman (1991) namely family, education, religion, community, and language attitudes strengthen the use and transmission of the Madurese language. Language maintenance strategies based on Holmes (2013) include intergenerational transmission, institutional support through programs such as Perbahasaan (a structured Madurese language practice activity), community involvement through cultural performances such as Sandur (traditional ritual dance-theater) and Manten (traditional wedding and ceremonial practices), and government support through the local content curriculum. Media and technology play a relatively limited role, as official communication platforms and written announcements within the Pesantren (Islamic boarding schools) predominantly employ Indonesian to ensure broader accessibility for students and parents from diverse linguistic backgrounds. The findings indicate that Pesantren creates a dynamic multilingual environment in which Madurese remains actively used in daily, educational, and cultural domains, highlighting its significant role in sustaining regional language and cultural identity amid modernizing pressures.